BAHA in children: Indications, results and complications - Reis, Cláudia (2014)
BAHA (Bone Anchored Hearing Aid) is used in external and middle ear malformations, chronic ear discharge, inoperable ossicular disease and as alternative to conventional hearing aids in case of unsuitability. This article describes the BAHA experience in Hospital Maria Pia – Centro Hospitalar do Porto Pediatrics Unit over the last decade, by retrospective study of 47 patients. The average audiometric gain was 33,9 dB compared to baseline values and 14,4 dB versus conventional hearing aids, with average hearing threshold with BAHA of 17,8 dB. There were no intra-operative complications. Postoperatively, 4 cases demanded surgical revision of the skin, in 2 cases there was no osseointegration of the implant and in 3 cases occurred implant extrusion following direct trauma. This study concludes that BAHA is an effective and safe method of hearing aid in children.